Evaluation of the quality of life in adolescents with acne - Reljić, Vesna; Maksiković, Nataša; Janković, Janko; Mijović, Biljana; Perić, Jelena; Janković, Slavenka (Vojnosanitetski pregled, 2014)
Background/Aim. Acne is well recognized condition that adversely affects quality of life (QoL) of the patients. The aim of this study was to determine the self-reported prevalence of acne and its main characteristics in high school pupils, and to assess their QoL. Methods. The cross-sectional study conducted in May 2011 comprised 440 pupils from Serbia (281 from Belgrade and 159 from Užice). Participation in the study was voluntary and anonymous. Two questionnaires were administered: a short demographic questionnaire, and Children’s Dermatology Life Quality Index (CDLQI). Internal consistency was assessed using the Cronbach’s alpha while item-total score correlations were assessed using Spearman’s correlation analysis. Results. The majority of the study population (84.3%) were girls, and 15.7% were boys. The total mean age of the pupils was 16.48 ± 0.55 years. A total of 228 (51.8%) pupils self-reported their acne with significantly higher prevalence in Užice (73.6%) than in Belgrade (39.5%). The mean CDLQI score was 3.55 with the similar quality of life impairment in adolescents from the two cities. The mean Cronbach’s alpha was 0.83. There was a statistically significant positive correlation between the mean overall CDLQI score and CDLQI subscale scores that ranged from 0.401 to 0.841. Conclusion. Our study confirmed that acne is associated with impairment in QoL that is in accordance with previous studies performed on teenagers. The CDLQI is a reliable and valid measure, and can be used as a practical tool for measuring the impact of acne on patients’ QoL.